2018
DOI: 10.1111/cas.13475
|View full text |Cite
|
Sign up to set email alerts
|

Plasma soluble podoplanin is a novel marker for the diagnosis of tumor occurrence and metastasis

Abstract: Podoplanin (PDPN) is expressed on many tumors and is involved in tumor metastasis. The objective of the present study was to develop an ELISA for determining soluble PDPN (sPDPN) levels as a potential novel tumor marker in plasma of patients with cancers for detection of tumor occurrence and metastasis. Mouse monoclonal antibodies (mAb) against human PDPN were developed and characterized. Two anti‐PDPN mAb, SZ‐163 and SZ‐168, were used in a sandwich ELISA to detect plasma sPDPN in patients with cancers and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 35 publications
1
22
0
2
Order By: Relevance
“…In bladder cancer, higher levels of soluble podoplanin in the serum of patients are associated with larger and more aggressive multifocal tumors [164]. Likewise, the levels of soluble podoplanin in plasma were found to increase in patients with a wide variety of cancers compared to normal individuals, as well as in patients with metastasis with respect to patients with non-metastatic tumors [165]. Interestingly, the levels of soluble podoplanin were reduced after treatment of patients with chemotherapy or surgery followed by chemotherapy, pointing to soluble podoplanin as a specific cancer biomarker [165].…”
Section: Significance Of Podoplanin Expression In Cancermentioning
confidence: 99%
“…In bladder cancer, higher levels of soluble podoplanin in the serum of patients are associated with larger and more aggressive multifocal tumors [164]. Likewise, the levels of soluble podoplanin in plasma were found to increase in patients with a wide variety of cancers compared to normal individuals, as well as in patients with metastasis with respect to patients with non-metastatic tumors [165]. Interestingly, the levels of soluble podoplanin were reduced after treatment of patients with chemotherapy or surgery followed by chemotherapy, pointing to soluble podoplanin as a specific cancer biomarker [165].…”
Section: Significance Of Podoplanin Expression In Cancermentioning
confidence: 99%
“…Our previous study found that SZ163 and SZ168 detected hPDPN in CHO/hPDPN, NCI-H226, and U87 cells but not CHO cells [24], indicating that SZ163 and SZ168 specifically recognize hPDPN. Flow cytometry assay showed that SZ163 and SZ168 also detected endogenous PDPN in the human cancer cell lines C8161 and CNE-2, similarly to the 18H5 as positive control antibody (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SZ163 and SZ168, two mouse anti-hPDPN mAbs, were developed as described previously [24]. A mouse anti-hPDPN mAb (18H5), a normal mouse IgG (ab188776), and a rabbit anti-hPDPN mAb (EPR7072) were purchased from Abcam (Cambridge, UK).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations